Intervensi Orang Tua dalam Rumah Tangga Anak pada Masyarakat Sei Lekop, Bintan: Tinjauaan Sosiologi Hukum Islam dan Strategi Membangun Keharmonisan Keluarga - Surya Fadhli; Rizki Amar; M. Rezeki Rachmatullah (CV. Creative Tugu Pena, 2024)
Parental intervention in children's households is a phenomenon that is often found in society, including in Sungai Lekop Village, East Bintan District. This research aims to identify the forms of parental intervention, analyze its impact on family harmony, and evaluate this phenomenon through the perspective of Sociology of Islamic Law and Salvador Minuchin's Family System Theory. This research uses a qualitative method with a descriptive-analytical approach. Data were obtained through in-depth interviews with families, community leaders, and related parties. The results show that parental intervention includes material support, advice, parenting, and decision-making in family life. While these interventions can strengthen family ties, in some cases, excessive intervention inhibits the independence of the couple. In the perspective of Islamic Legal Sociology, parental intervention is part of the responsibility to ensure the welfare of children, but it needs to be balanced with respect for the autonomy of spouses. Salvador Minuchin's Family Systems Theory emphasizes the importance of healthy boundaries between generations to prevent family dysfunction. This research recommends applying the principle of balance between the rights and obligations of parents and spouses to support household harmony.